Dependence on hypnotics: a comparative study between chronic users of benzodiazepines and Z-drugs - Curado,Daniela F. (2022)
Objective: To evaluate dependence among chronic benzodiazepine and Z-drug users in Brazil. Methods: Chronic users of benzodiazepines (n=94), Z-drugs (n=74), or both (n=11) were recruited from the community, underwent a psychiatric evaluation and completed self-report instruments on hypnotic dependence, insomnia, anxiety, and depression. Users of benzodiazepines and Z-drugs were compared using t-tests, and logistic regression models were employed to explore significant predictors of a dependence diagnosis. Results: There was no difference in the prevalence of dependence among benzodiazepine (77.2%) and Z-drug (69.4%) users. Benzodiazepine users reported increased psychosocial aspects of dependence, anxiety, and depression. Preoccupation with the availability of medication (prevalence ratio [PR] = 2.39 [1.15-5.20]) and insomnia (PR = 1.10 [1.02-1.19]) were associated with a diagnosis of dependence (n=175). Conclusion: The prevalence of dependence was similar among both drug classes. The increased self-reported dependence, anxiety, and depression among benzodiazepine users may be due to behavioral rather than pharmacological aspects of medication use. Behaviors related to hypnotic use were important predictors of dependence.